Embryonic ILC-poiesis across tissues - Hernández-Torres, Daniela Carolina; Stehle, Christina (Frontiers in Immunology, 2022)
The family of innate lymphoid cells (ILCs), consisting of Group 1 ILCs (natural killer cells and ILC1), ILC2, and ILC3, are critical effectors of innate immunity, inflammation, and homeostasis post-natally, but also exert essential functions before birth. Recent studies during critical developmental periods in the embryo have hinted at complex waves of tissue colonization, and highlighted the breadth of multipotent and committed ILC progenitors from both classic fetal hematopoietic organs such as the liver, as well as tissue sites such as the lung, thymus, and intestine. Assessment of the mechanisms driving cell fate and function of the ILC family in the embryo will be vital to the understanding ILC biology throughout fetal life and beyond.